(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Obtaining cells of Physalis pubescens is of interest for studies of primary and secondary metabolic pathways, in the search for new active molecules. Our objectives were to evaluate the regeneration potential of explants from different parts of the plant, growth regulators to be used, and the determination of the growth curve of the callus. We used explants of leaf, root, stem and petiole, cultured on Murashige and Skoog medium with different concentrations of 6-benzylaminopurine and a-naphthaleneacetic acid. The explants from stem and petiole had a higher regeneration potential of the shoot to the treatment with 0.5 mg L-1 6-benzylaminopurine, and the explants of leave and root emitted more roots, with lower production of callus. The tests showed that the regeneration of the whole plant should be done in two steps: cultivation for shoot regeneration and transplantation to a new rooting medium. The growth of callus showed five distinct phases, with accumulation of phenols in the final stages of growth. The levels of soluble sugars increased with age, while reducing sugars showed variations, with higher concentrations in the initial stages of cultivation, with fall and rise again at the final evaluation (28th day).